Pituitary hyperplasia secondary to acquired hypothyroidism: case report - Bellizzi Maria; Failo Riccarda; Rozzanigo Umberto; Franceschi Roberto; Di Palma Annunziata (BMC, 2011)
Abstract Objective and Importance despite recent progress in imaging, it is still difficult to distinguish between pituitary adenoma and hyperplasia, even using Magnetic Resonance Imaging (MRI) with gadolinium injection. We describe an example of reactive pituitary hyperplasia from primary hypothyroidism that mimicked a pituitary macroadenoma in a child. Clinical Presentation a 10 year old boy presented with headache and statural growth arrest. MRI revealed an intrasellar and suprasellar pituitary mass. Endocrine evaluation revealed primary hypothyroidism. Intervention the patient was started on levothyroxine with resolution of the mass effect. Conclusion primary hypothyroidism should be considered in the differential diagnosis of solid mass lesions of the pituitary gland. Examination of thyroid function in patients with sellar and suprasellar masses revealed by MRI may avoid unnecessary operations which can cause irreversible complications.